2008
DOI: 10.1007/s11010-008-9984-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Epstein-Barr virus (EBV) lytic cycle in vitro causes oxidative stress in lymphoblastoid B cell lines

Abstract: Here, we investigated the effect of induction of the Epstein-Barr virus (EBV) viral lytic cycle on the oxidant/antioxidant balance in three lymphoblastoid cell lines: B95-8, Raji, and LCL C1. The induction of the EBV lytic cycle was done by a non-stressing dose of 12-0-tetradecanoylphorbol-13-acetate (8 nM). Oxidative stress was assessed by measuring malondialdehyde as a parameter of lipid peroxidation, the levels of glutathione, and the activities of three antioxidant enzymes (superoxide dismutase, catalase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The autophagy machinery probably degrades cellular or viral factors that repress EBV lytic reactivation. Additionally, the induction of the EBV lytic cycle causes endoplasmic reticulum and oxidative stresses (71), and autophagic induction may prevent stress-induced cell death, eventually favoring lytic development. This study also found that 3-MA, an inhibitor of autophagy, led to viral particles being retained within cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy machinery probably degrades cellular or viral factors that repress EBV lytic reactivation. Additionally, the induction of the EBV lytic cycle causes endoplasmic reticulum and oxidative stresses (71), and autophagic induction may prevent stress-induced cell death, eventually favoring lytic development. This study also found that 3-MA, an inhibitor of autophagy, led to viral particles being retained within cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress activates the EBV early gene BZLF-1, which causes the reactivation of EBV lytic cycle [114]. This has been proposed to play an important role in the pathogenesis of EBV-associated diseases including malignant transformations [115, 116]. …”
Section: Viruses Cause Oxidative Stress In Host Cellsmentioning
confidence: 99%
“…There is evidence that viral infections (hepatitis C, HIV and influenza) are associated with an increased production of ROS and that could be involved in the pathogenesis [33,34]. EBV infection is also associated with the production of ROS [35,36] and this has been reported in EBV-associated diseases such as Burkitt’s lymphoma and NPC [37,38]. These studies imply that ROS are incriminated in EBV-associated disease.…”
Section: Introductionmentioning
confidence: 99%